TEACHER PROFESSIONAL COMPETENCE IN THE SPHERE OF PUPILS’ SCIENTIFIC LABOUR MANAGEMENT - Olena V. Anishchenko (Інформаційні технології і засоби навчання, 2010)
The article deals with the analysis of the teacher professional competence in the sphere of pupils’ scientific labour management. The main teacher professional competence components are characterized in the context of students’ and pupils’ scientific labour management.